2020
DOI: 10.1002/ece3.6057
|View full text |Cite
|
Sign up to set email alerts
|

Elevated precipitation alters the community structure of spring ephemerals by changing dominant species density in Central Asia

Abstract: Global climate change is one of the most pressing conservation challenges; in particular, changes in precipitation regimes have already substantially influenced terrestrial ecosystems. However, the mechanisms influencing precipitation changes on individual plants and the plant communities in desert grasslands have yet to be fully elucidated. We therefore examine the influence of increased precipitation on plant community compositions in the Gurbantunggut Desert, Xinjiang, northwestern China, from 2005 to 2009.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
(101 reference statements)
0
6
1
Order By: Relevance
“…Furthermore, because the dominant species is a perennial herb whose root system is primarily distributed in the soil surface layer (Sims et al, 1978), the dominant species responds more clearly to drought (Wraith et al, 1995). In addition, another study has found that increased precipitation significantly promotes the density of dominant species in semi‐arid ecosystems (Jia et al, 2020), which was inconsistent with our results. We found that increased precipitation did not significantly promote the growth of the dominant species.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, because the dominant species is a perennial herb whose root system is primarily distributed in the soil surface layer (Sims et al, 1978), the dominant species responds more clearly to drought (Wraith et al, 1995). In addition, another study has found that increased precipitation significantly promotes the density of dominant species in semi‐arid ecosystems (Jia et al, 2020), which was inconsistent with our results. We found that increased precipitation did not significantly promote the growth of the dominant species.…”
Section: Discussioncontrasting
confidence: 99%
“…In dryland, there are a special group of herbs called “ephemeral plants” that tend to grow fast, thereby completing their life cycles faster than other herbaceous plants [ 23 , 24 , 27 ]. In temperate desert ecosystems, spring ephemerals play an important role in the community structure [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, ephemeral plants were referred to as spring ephemeral plants, which germinate in early spring and generally complete their life cycle in 60–70 days (before the arrival of summer drought, dying before or in July) [ 27 , 28 , 35 , 36 , 37 ]. Therefore, according to their life history, these special plants were distinguished from the other long-lived herbaceous plants, following the Flora Reipublicae Popularis Sinicae ( , accessed on 5 December 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between precipitation and spring ephemeral growth seems to be incomplete in the literature. Matthews and Mazer (2016) reported delays in flowering with higher precipitation levels in Western North America, but most other spring ephemeral precipitation research has focused on desert climates ( Chen et al 2019 ; Jia et al 2019 ; Rominger et al 2019 ; Mu et al 2021 ). Despite the depth of research into the effects of temperature on spring ephemeral reproductive responses, no studies to our knowledge have examined how weather conditions of past seasons, including both temperature and precipitation, influence a change in aboveground cover for the following year.…”
Section: Introductionmentioning
confidence: 99%